Healthcare workers in the barangay a correlational analysis of resilience and job performance of barangay healthcare workers (BHW's) in the Municipality of Miagao, Iloilo - Sequido, Clarence F.
At the onset of the pandemic lockdown the BHWs were one of those who were first mobilized by the government to assist and monitor the basic health situation of communities in the barangays. The unfamiliarity of the conditions presented by the pandemic is expected to affect the BHW functioning and their job performance. This study aimed to determine the relationship between the traits of resilience and job performance of the BHWs in the Municipality of Miagao, Iloilo. Additionally, the study examined differences in resilience and job performance across three strata of BHWs categorized by distance from the Rural Health Unit. To measure the level of resilience the researcher used the modified Nicholson Resilience Scale. In measuring Job performance, the researcher used the modified Koopmans Work Performance Scale. The mean scores revealed that BHWs have an exceptionally high resilience level and high levels of job performance. To test the relationship of the variables , the non-parametric correlation analysis was used. The results revealed that there is a significant relationship between the resilience and job performance of the BHWs. This study concludes that increases in the ability of BHWs to bounce back from the challenges posed by the pandemic is associated with increases in their job performance levels. Comparison across strata revealed that only the job performance variable differed significantly, specifically between BHWs based closest to the RHU and those farthest from the RHU. No significant difference in resilience across strata was found.